Computation of airfoil boundary layer - Nurfhaizatul Aqma, Chik Aik (2007)
Computation of Airfoil boundary layer is an analysis of flow around an airfoil using a CFD commercial packages, GAMBIT/FLUENT. The simulation process will be done to revise the basic theory of complex fluid flow phenomena laminar and turbulent flow around airfoil. The simulation was done for these flows ensuring in the process that the computations are numerically reliable. Experimental result by Nakayama will be compared with the simulation result for turbulent flow. The flow is 2-dimensional and the grid is all 'C' types meshes. It can be computed as both at low-Reynolds number laminar case and high-Reynolds number turbulent case. The domain is chosen so that the boundaries are far away from the airfoil itself. This choice allows for the use of pressure far-field boundary condition. A number of predefined grids are used to investigate the effect of different grid densities and discretization schemes. The flow is set to come at different angles of coincidence and the velocity magnitude. The discretization schemes used is 1st Order UPWIND scheme and QUICK scheme. It shows that by using QUICK schemes the convergence is far quicker than the 1St Order UPWIND schemes. The drag and lift coefficient obtain for all cases is to be noted. There are two models being tested for turbulent flow, the SpalartAllmaras and k- F, Model. The Spalart-Allmaras Model shows a good prediction of the velocity profiles compared to the k- F Model.